THE ROLES AND POLICIES FOR THE USE OF TELEMEDICINE IN HANDLING COVID-19 SELF-ISOLATION: LITERATURE REVIEW - Yonathan, Rafika Stany; Nadjib, Mardiati (UI Scholars Hub, 2022)
The current COVID-19 pandemic has had various impacts on the world. The unpredictable spike in cases led to an explosion in patient numbers. The problem of limited treatment facilities forces patients to self- isolate at home. Along with technological advances, various facilities have also been created, one of which is telemedicine. This study aims to look at the role of telemedicine as a strategy for handling COVID-19 self-isolated patients in various countries. This study was conducted descriptively with a literature review. The search was carried out on articles published in Indonesian and English through Google Scholar, Pubmed, and Science Direct searches with the keywords COVID-19, home isolation, self-isolation, telemedicine, and telehealth. The search results obtained that the handling of COVID-19 patients in self-isolation with telemedicine is a solution to the need for monitoring patient health, where hospitals have difficulty being able to serve all patients who need hospitalization. It can be concluded that COVID-19 is a newly emerging disease, clinical symptoms and emergencies of each patient can certainly be different and difficult to predict. Telemedicine as a remote health service can be a means to facilitate clinical monitoring of patients during self-isolation. The implementation of telemedicine ensures the continuity of health services quite effectively and efficiently, the way telemedicine works helps protect patients and health workers from exposure to infection and reduces the burden on hospitals, so it is quite appropriate to be used as a strategy in handling if there is a spike in COVID-19 cases in the future or application to other similar circumstances.